Analisis Hubungan Mahasiswa KKN dengan Motivasi Belajar Siswa di SMPN 3 Maliku - Nur Fitriani; Nurmasari Nurmasari; Dina Mariana; Fatma Fatma; Rizky Andrianto; Muhammad Ridwannor Kharysmy; Gito Supriyadi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research discusses the relationship between KKN students and the learning motivation of students at SMPN 3 Maliku. The purpose of this research is to determine whether there is a relationship between KKN students and the learning motivation of students at SMPN 3 Maliku using correlation tests, to see the relationship and how strong that relationship is. Using a quantitative research method with a PAR approach, the data collection technique employs a questionnaire with a Simple Random Sampling selection and determines the sample size using the Solvin Formula. The results of this study indicate that there is a relationship between KKN students and students' learning motivation of 0.877, which means that KKN students have a perfect relationship or correlation.